Clinical management of difficult to treat macroprolactinomas. Issue 3 (4th May 2019) - Sahakian, Nicolas; Castinetti, Frederic; Dufour, Henry; Graillon, Thomas; Romanet, Pauline; Barlier, Anne; Brue, Thierry; Cuny, Thomas
ABSTRACT: Introduction : Prolactinomas represent the most common pituitary adenomas encountered in the clinic. While a majority of these tumors will be successfully treated by dopamine agonist (DA) such as cabergoline, their management becomes problematic since a resistance to DA can occur and/or if the tumor displays features of aggressiveness, two conditions that are closely related. Areas covered : Epidemiology and medical treatment of prolactinomas; resistance to DA and molecular basis of DA-resistance; therapeutical alternatives in case of DA-resistant Prolactinomas and therapies in development; summarizing conclusions. Expert opinion : The management of DA-resistant prolactinomas requires a multidisciplinary approach by an expert team. Along with discussions about surgery with or without gamma knife radiosurgery, genetic screening for multiple endocrine neoplasia type 1 (MEN1) syndrome is actively discussed in a case-by-case approach. In case of surgery, a careful analysis of the tumor sample can provide information about its aggressivity potential according to recent criteria. Ultimately, temozolomide can be indicated if the tumor is rapidly growing and/or threatening for the patient.